Guidebook to the extracellular matrix and adhesion proteins - Kreis, Thomas; Vale, Ronald (Oxford University Press, 1993)
These Sambrook and Tooze Guidebooks provide students and professionals with a unique reference source to the latest information available on the proteins involved in cell adhesion, the cytoskeleton, and the extracellular matrix. This volume provides a concise compendium of the proteins found in the extracellular matrix and those known to be involved in cell-cell contact and adhesion. Organized alphabetically, it summarizes the essential features of these proteins, giving key references and drawing together information from widely scattered sources. This is the only book where information on so many related proteins can be found. Designed to explain the essentials of each protein in an accessible manner, the Guidebooks are also referenced for in-depth reading and provide excellent overviews.
Keywords: Buňky; Proteiny; proteiny; buněčná adheze; biochemie; Cell Adhesion; Proteins; Extracellular Matrix Proteins; extracelulární matrix - proteiny; molekulární biologie, molekulární medicína